Ferumoxytol-enhanced magnetic resonance imaging assessing inflammation after myocardial infarction. Issue 19 (22nd June 2017) - Stirrat, Colin G; Alam, Shirjel R; MacGillivray, Thomas J; Gray, Calum D; Dweck, Marc R; Raftis, Jennifer; Jenkins, William SA; Wallace, William A; Pessotto, Renzo; Lim, Kelvin HH; Mirsadraee, Saeed; Henriksen, Peter A; et al.
Abstract : Objectives: Macrophages play a central role in the cellular inflammatory response to myocardial infarction (MI) and predict subsequent clinical outcomes. We aimed to assess temporal changes in cellular inflammation and tissue oedema in patients with acute MI using ultrasmallsuperparamagnetic particles of iron oxide (USPIO)-enhanced MRI. Methods: Thirty-one patients were recruited following acute MI and followed up for 3 months with repeated T2 and USPIO-enhanced T2*-mapping MRI. Regions of interest were categorised into infarct, peri-infarct and remote myocardial zones, and compared with control tissues. Results: Following a single dose, USPIO enhancement was detected in the myocardium until 24 hours (p<0.0001). Histology confirmed colocalisation of iron and macrophages within the infarcted, but not the non-infarcted, myocardium. Following repeated doses, USPIO uptake in the infarct zone peaked at days 2–3, and greater USPIO uptake was detected in the infarct zone compared with remote myocardium until days 10–16 (p<0.05). In contrast, T2-defined myocardial oedema peaked at days 3–9 and remained increased in the infarct zone throughout the 3-month follow-up period (p<0.01). Conclusion: Myocardial macrophage activity can be detected using USPIO-enhanced MRI in the first 2 weeks following acute MI. This observed pattern of cellular inflammation is distinct, and provides complementary information to the more prolonged myocardial oedema detectable using T2 mapping. This imaging technique holds promise as a non-invasive method of assessing and monitoring myocardial cellular inflammation with potential application to diagnosis, risk stratification and assessment of novel anti-inflammatory therapeutic interventions. Trial registration number: Trial registration number: 14663. Registered on UK Clinical Research Network (http://public.ukcrn.org.uk) and also ClinicalTrials.gov (https://clinicaltrials.gov/ct2/show/NCT02319278?term=DECIFER&rank=2 ).